2010
DOI: 10.1116/1.3359593
|View full text |Cite
|
Sign up to set email alerts
|

Precision laser micromachining of trenches in GaN on sapphire

Abstract: Trench formation for device isolation on GaN light-emitting diode (LED) wafers via nanosecond ultraviolet laser micromachining is demonstrated. Trenches with smooth sidewalls and flat bottom surfaces are produced. Unlike wafer scribing with laser beams, the formation of trenches requires that the incident fluence is sufficient for laser ablation of GaN, yet low enough to prevent ablation of the sapphire substrate. Owing to the dissimilar ablation thresholds between GaN and sapphire, the etch process terminates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A schematic diagram of the laser micromachining setup is shown in figure 1 [2]. The laser source used was a thirdharmonic neodymium-doped yttrium lithium fluoride diodepumped solid-state laser (Spectra Physics).…”
Section: Methodsmentioning
confidence: 99%
“…A schematic diagram of the laser micromachining setup is shown in figure 1 [2]. The laser source used was a thirdharmonic neodymium-doped yttrium lithium fluoride diodepumped solid-state laser (Spectra Physics).…”
Section: Methodsmentioning
confidence: 99%
“…Y.H. Mak et al [12] showed that micro-trenches with different topographies can be obtained precisely by controlling the focus offset and pulse energy of the laser beam. For example, in Figure 3(a), the sample is positioned near the focal plane (300 μm from focal plane); the laser beam ablates both the GaN and sapphire layers.…”
Section: Topography Of Laser Micromachiningmentioning
confidence: 99%
“…[10][11][12][13][14][15] Especially for transparent materials, different methods have been used to generate high-aspect-ratio micro-holes such as combination with chemical etching, 4,5 beam shaping, 2,6 and liquid-assisted drilling from rear surface. 1,3,7 However, the fs laser sources, generally, are traditional solid-state lasers, which are expensive, bulky, and need regular maintenance.…”
Section: Introductionmentioning
confidence: 99%